2022
DOI: 10.1016/j.frl.2021.102624
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 impact on commodity futures volatilities

Abstract: COVID-19 pandemic has affected almost all aspects of the global economy, especially commodity futures markets, due to the disruption risk of global supply chains from the pandemic lockdown. This paper extends ARMA-GARCH models to investigate the pandemic impact on both long-run and short-term volatilities of four major commodity futures. Model-fitting results reveal that the pandemic event has enhanced long-run volatilities for all futures returns, while the daily COVID-19 infection speed has mixed effects on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 13 publications
0
17
0
Order By: Relevance
“…irdly, different from prior papers that employed merely the worldwide pandemic cases [3,24,43,44], our econometric investigation covers both new cases of COVID-19 pandemic globally and in Europe. As well, contrary to prior papers that used the price of WTI crude oil [1-4, 7, 8, 24-26, 29, 33, 35, 39, 43, 45-56], Brent crude oil [4,7,8,15,24,26,36,37,43,44,46,47,49,51,52,[54][55][56], Dubai crude oil [4,8], NYMEX's oil [26,55,57], or carbon futures [14], the current study covers the daily returns of the Physical Electricity Index, Amsterdam Power Exchange Electricity Netherlands Average All Hours and, London Natural Gas Index United Kingdom Pence Per 100000 British ermal Units. Not least, different from prior papers focused on time-frequency connectedness [32,42,55,56,58], our quantitative framework covers several techniques such as GARCH estimation, autoregressive distributed lag (ARDL) models, as well as vector autoregressive (VAR) models.…”
Section: Introductionmentioning
confidence: 89%
See 3 more Smart Citations
“…irdly, different from prior papers that employed merely the worldwide pandemic cases [3,24,43,44], our econometric investigation covers both new cases of COVID-19 pandemic globally and in Europe. As well, contrary to prior papers that used the price of WTI crude oil [1-4, 7, 8, 24-26, 29, 33, 35, 39, 43, 45-56], Brent crude oil [4,7,8,15,24,26,36,37,43,44,46,47,49,51,52,[54][55][56], Dubai crude oil [4,8], NYMEX's oil [26,55,57], or carbon futures [14], the current study covers the daily returns of the Physical Electricity Index, Amsterdam Power Exchange Electricity Netherlands Average All Hours and, London Natural Gas Index United Kingdom Pence Per 100000 British ermal Units. Not least, different from prior papers focused on time-frequency connectedness [32,42,55,56,58], our quantitative framework covers several techniques such as GARCH estimation, autoregressive distributed lag (ARDL) models, as well as vector autoregressive (VAR) models.…”
Section: Introductionmentioning
confidence: 89%
“…Furthermore, concern for a worldwide recession has generated unavoidable systemic risks in the energy markets, exposing investors who own oil-derived securities to detrimental changes in crude prices [46]. e study by Zhang and Wang [57] demonstrated that the disease has increased long-term volatility for all future returns. Also, Shaikh [52] proved that through disease eruptions, the WTI crude oil market exhibited exceptional overreaction and dealt at an extremely volatile level.…”
Section: Background Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…Second, international oil markets are vital to financial and economic stability worldwide, as numerous studies indicate that oil prices have a strong linkage to international stock markets (Ghosh & Kanjilal, 2016 ), to other commodity prices (Sun et al, 2021 ) and economic factors, such as GDP and interest rates (Lian et al, 2020 ; Urom et al, 2021 ). Finally, the COVID‐19 pandemic is a dramatic public crisis that has affected almost all aspects of the worldwide economy and commodity price volatilities (Zhang & Wang, 2021 ), especially oil futures prices, which move in an extremely volatile way. Therefore, investigation of the impacts of COVID‐19 on US and Chinese oil futures markets' return and volatility spillover effects is important to understand the effect the pandemic had on the world economy.…”
Section: Introductionmentioning
confidence: 99%